2020
DOI: 10.5741/gems.56.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Oxygen Stable Isotope Ratios of Dolomite-Related Nephrite: Relevance for its Geographic Origin and Geological Significance

Abstract: N ephrite is a near-monomineralic rock composed of tremolite-actinolite, Ca 2 (Mg,Fe) 5 Si 8 O 22 (OH) 2. It occurs worldwide (figure 1) and is classified as dolomite-related or serpentine-related according to the different parent rocks and ore-hosting rocks, and both types form by metasomatism (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…H-O isotope tracing of mineralized hydrothermal fluids needs calculations of H-O isotopic values by nephrite mineralization temperature intervals to calculate the values of H-O isotopes and thus identify the source of mineralized hydrothermal fluids (Yui and Kwon, 2002). According to Liu et al and Gao et al, two methods are typically used to determine the temperature of nephrite mineralization: 1) the first is based on the temperature interval of inclusions in nephrite minerals, such as calcite (250 °C in average) (Liu et al, 2011) and pyrite (327 °C in average) (Xu et al, 2014), 2) the second is based on the temperature interval of 330-450 °C for the mineralization of the skarn (Gao et al, 2020). Graham et al concluded that although hydrogen isotopic values reflects the temperature of nephrite mineralization and type of mineraliztion solution, the variation of hydrogen isotopic values of nephrite with temperature is very insignificant in the temperature range of 350-650 °C.…”
Section: Application Of Hydrogen and Oxygen Isotopesmentioning
confidence: 99%
“…H-O isotope tracing of mineralized hydrothermal fluids needs calculations of H-O isotopic values by nephrite mineralization temperature intervals to calculate the values of H-O isotopes and thus identify the source of mineralized hydrothermal fluids (Yui and Kwon, 2002). According to Liu et al and Gao et al, two methods are typically used to determine the temperature of nephrite mineralization: 1) the first is based on the temperature interval of inclusions in nephrite minerals, such as calcite (250 °C in average) (Liu et al, 2011) and pyrite (327 °C in average) (Xu et al, 2014), 2) the second is based on the temperature interval of 330-450 °C for the mineralization of the skarn (Gao et al, 2020). Graham et al concluded that although hydrogen isotopic values reflects the temperature of nephrite mineralization and type of mineraliztion solution, the variation of hydrogen isotopic values of nephrite with temperature is very insignificant in the temperature range of 350-650 °C.…”
Section: Application Of Hydrogen and Oxygen Isotopesmentioning
confidence: 99%
“…Ratios of iron to magnesium and concentrations of chromium, nickel, cobalt, and manganese distinguish para-nephrite from orthonephrite. Along with trace element concentrations, hydrogen and oxygen stable isotopic ratios have been used to determine the geographic origin of select dolomite-related nephrite deposits (Gao et al, 2020). As many concentrations of minor elements overlap for both types of nephrite, expanding the range of trace element determinations and overall geochemical datasets could refine models and criteria for distinguishing dolomite-related and serpentinite-related nephrite.…”
Section: Exogenic Deposits Representing Secondarymentioning
confidence: 99%
“…Researchers have achieved informative results by utilizing trace elements and hydrogen-oxygen isotopes to identify geographical origins. [16][17][18] Nevertheless, this oen necessitates complex sample pretreatment, potentially damaging the samples. Nonetheless, distinguishing the origins of nephrite jade remains challenging, especially regarding rapid discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have achieved informative results by utilizing trace elements and hydrogen-oxygen isotopes to identify geographical origins. [16][17][18] Nevertheless, this oen necessitates complex sample pretreatment, potentially damaging the samples.…”
Section: Introductionmentioning
confidence: 99%